MEWUJUDKAN LINGKUNGAN SEKOLAH BERWARNA: REVITALISASI LAPANGAN DAN PEMBUATAN SARANA PERMAINAN SEKOLAH DASAR NEGERI 1 WIDORO - Salmanhaji Arbai; Yuris Indria Persada; Devina Kurniawati; Adira Suara Hakiki; Beril Jagad Wahyu Abadi; Sandhi Wildan Wicaksana (Wisesa: Jurnal Pengabdian Masyarakat, 2025)
English A school environment that supports children's physical and visual activities plays an important role in stimulating the motor, cognitive and psychosocial growth of primary school students. However, limited open space facilities are still a common problem, especially in rural schools. This community service program aims to revitalize the field and create educational-based children's play facilities at SD Negeri 1 Widoro, Gandusari District, Trenggalek Regency. The activity method includes initial observation, preparation of intervention design, implementation of revitalization by the KKN team of State University of Malang 2025, and evaluation based on visual documentation. The results showed a significant transformation in the school field area, which is now divided into three multifunctional sports fields (futsal, volleyball, and sepak takraw) with different color lines, as well as the addition of four types of outdoor educational games, namely engklek, floor twister, spiral alphabet zone, and directional jump circle. This activity succeeded in creating a more attractive, fun and functional learning environment, as well as encouraging students' active participation in physical activity and social interaction. Visual documentation shows a marked improvement in aesthetics and student engagement. This program is expected to become a model for participatory and sustainable development of school outdoor facilities